Clinical characteristics and prognosis of elderly patients with colorectal cancer: Comparison between surgical resection and supportive care. Issue 7 (19th February 2021) - Kim, Soohwan; Kim, Dong Suk; Soh, Jae Seung; Lim, Sang-Woo; Lim, Hyun; Kang, Ho Suk; Kim, Jong Hyeok
Abstract : Abstract: Elderly colorectal cancer (CRC) patients tend to avoid standard treatment, especially curative surgical resection, because of concerns about surgical complications or underlying diseases. This study is intended to compare clinical characteristics and prognosis between patients who had undergone surgical resection and received supportive care, and to evaluate the usefulness of surgical treatment in elderly patients. A total of 114 patients aged ≥80 years who were diagnosed with CRC were analyzed retrospectively. Of these patients, 73 patients underwent surgical resection for malignancy and 41 patients received supportive care. Clinicopathological factors and overall survival (OS) rates were compared. The s urgical resection group had better Eastern Cooperative Oncology Group performance status, American Society of Anesthesiologists (ASA) physical status, and a lower stage than did the supportive-care group. The 3-year OS rate of the surgical group was significantly higher than that of the supportive-care group (60.7% vs 9.1%, P < .001). In extremely elderly patients (age ≥85 years), the surgical group showed a better 3-year OS rate than did the supportive-care group (73.9% vs 6.3%, P < .001), although Eastern Cooperative Oncology Group performance status and ASA physical status were not different. The post-operative mortality rate was 2.7%. In the analysis of risk factors related to survival, surgical resection was a good prognostic factor. Surgical treatment in elderly CRC patients showed a survival benefit, even in the extremely elderly patients. Surgical resection for CRC in elderly patients can be considered to improve survival.